Penerapan Error Correction Model dalam Analisis Determinan Ekspor Teh di Indonesia Tahun 1980 – 2023 - Ningrum, Icha Wahyu Kusuma; Agustini, Peni (Politeknik Statistika STIS, 2025)
Tea is a crucial commodity in the plantation subsector, strategically contributing to the national economy, both as a source of state revenue through exports and as a provider of employment. However, Indonesia's tea export volume has been unstable and has tended to decline since 2008. If this trend continues, there are concerns that Indonesia will lose its capacity to export tea sustainably in the long term. Therefore, a comprehensive analysis of the factors influencing tea export volume, both in the short and long term, is needed to support the formulation of targeted policies. This study uses an Error Correction Model (ECM) approach with data covering 1980 to 2023. The estimation results indicate that in the long term, tea production, exchange rates, and world coffee prices significantly influence tea export volume. Meanwhile, in the short term, only tea production and world coffee prices significantly influence Indonesian tea exports. Therefore, the recommendation is for stakeholders to use total tea production, the movement of the rupiah exchange rate against the US dollar, and the price dynamics of substitute commodities such as coffee as the main indicators in formulating export strategies. This strategy is expected to encourage a sustainable increase in the volume of Indonesian tea exports in the global market.